Teachers' goal orientations: Effects on classroom goal structures and emotions. (17th November 2016) - Wang, Hui; Hall, Nathan C.; Goetz, Thomas; Frenzel, Anne C.
Abstract : Background: Prior research has shown teachers' goal orientations to influence classroom goal structures (Retelsdorf et al ., 2010, Learning and Instruction, 20, 30) and to also impact their emotions (Schutz et al., 2007, Emotion in education, Academic Press, Amsterdam, the Netherlands). However, empirical research evaluating possible causal ordering and mediation effects involving these variables in teachers is presently lacking. Aim: The present 6‐month longitudinal study investigated the relations between varied motivational, behavioural, and emotional variables in practising teachers. More specifically, this study examined the reciprocal, longitudinal relations between teachers' achievement goals, classroom goal structures, and teaching‐related emotions, as well as cumulative mediational models in which observed causal relations were evaluated. Samples: Participants were 495 practising teachers from Canada (86% female, M  =   42 years). Methods: Teachers completed a web‐based questionnaire at two time points assessing their instructional goals, perceived classroom goal structures, achievement emotions, and demographic items. Results: Results from cross‐lagged analyses and structural equation modelling showed teachers' achievement goals to predict their perceived classroom goal structures that, in turn, predicted their teaching‐related emotions. Conclusions: The present results inform both Butler's (2012, Journal of Educational Psychology, 104, 726) theory on teachers' achievement goals and Frenzel's (2014, International handbook of emotions in education, Routledge, New York, NY) model of teachers' emotions in showing teachers' instructional goals to both directly predict their teaching‐related emotions, as well as indirectly through the mediating effects of classroom goal structures.